Ethical and Legal Considerations in AI-Driven Health Cybersecurity - Krunal Manilal Gala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the ethical and legal challenges of implementing AI in health cybersecurity. It examines key issues including data privacy, informed consent, algorithmic bias, and balancing innovation with regulation. The rapid growth of AI in healthcare cybersecurity offers significant benefits but also introduces complex risks. The article analyzes data minimization, anonymization, bias mitigation, adaptive regulation, and international cooperation considerations. It presents data on the current landscape and proposes frameworks to address challenges. Overall, the article aims to provide a comprehensive overview of how to harness AI’s potential for protecting health data while respecting patient rights and navigating evolving regulatory requirements.